Yoruba Films and the Problem of Toneless Orthography - Fadoro, J.O. (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Much research attention has been devoted to Yoruba films, and the prominent position they now occupy in Nigeria. However, to the best of our knowledge, none of these research works has attempted to take a critical look at the problem associated with the use of tones and diacritics in YoruÌ€baÌ films. The major issue that engages our attention in this work is the problem of ambiguity occasioned by producers refusal to make adequate use of tones and diacritics in writing the titles of their films. Through the purposive sampling method, fifteen films were carefully selected and watched. In a tabular form, the researcher listed out these titles, their possible interpretations, the intended titles and the procedure of getting the real titles was analysed.